Guided Inquiry-Based Learning in Biotechnology: Effects on Students’ Scientific Attitudes and Academic Achievement at Menglait Middle School Brunei Darsussalam - Ramli, Mohammad; Bohori, Rozikin (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study investigates the effects of guided inquiry-based learning on students’ scientific attitudes and academic achievement in biotechnology at Menglait Middle School, Brunei Darussalam. Employing a quasi-experimental design, two groups of Year 9 students were involved: the experimental group received biotechnology instruction through guided inquiry-based learning, while the control group experienced conventional teaching methods. Data were collected using a scientific attitude questionnaire and a standardized academic achievement test in biotechnology. The findings revealed a statistically significant improvement in both scientific attitudes and academic achievement among students in the experimental group compared to the control group. Guided inquiry not only fostered curiosity and a more positive attitude toward science but also enhanced students’ conceptual understanding and problem-solving skills. These results underscore the importance of implementing inquiry-based approaches in science education to promote deeper learning and attitudinal development. The study recommends integrating guided inquiry strategies into the science curriculum to support 21st-century learning goals. Moreover, teacher training programs should emphasize the facilitation of inquiry to ensure effective implementation. This research contributes to the growing body of evidence highlighting the pedagogical value of inquiry-based learning in secondary education, particularly in the context of biotechnology, a subject critical for scientific literacy in modern society.